USE OF CONSTRUCTION WASTE IN MANUFACTURING ENVIRONMENTALLY FRIENDLY CONCRETE BRICKS - Satrio, Muji; Rivai, Syafriman; Nasution, Ridwan (PT Inovasi Pratama Internasional, 2024)
The purpose of this research is to evaluate the potential of construction waste generated by the construction industry as an alternative raw material in the manufacture of environmentally friendly concrete bricks. Research the method and process of concrete brick production using construction waste as the main raw material. Analyze the physical and mechanical properties of concrete bricks produced from construction waste and compare them with conventional concrete bricks. The approach used in this research is an integrated qualitative-quantitative approach. The qualitative approach was used to identify the characteristics and physico-chemical properties of the construction waste used. Meanwhile, the quantitative approach was used to test the quality of the concrete bricks produced. This research used an experimental design. Experiments were conducted in a construction laboratory with strict control of the variables that can affect the quality of concrete bricks. The result of this study is that the utilization of construction waste in the manufacture of environmentally friendly concrete bricks has been shown to enable a reduction in the use of natural raw materials and reduce the environmental impact of concrete brick production. The use of construction waste affects the quality of concrete bricks, including strength, durability, and other physical properties. This research provides an in-depth insight into how to optimally utilize construction waste without compromising product quality. The use of construction waste in concrete brick production can reduce the carbon footprint and other environmental impacts, helping to promote more sustainable construction practices.